An Act of Auto‐Eroticism: Self‐Urethral Insertion of Sewing Needle by an Old Man—A Case Report With Literature Review - Rao Nouman Ali; Sohaib Irfan; Wajiha Irfan; Muhammad Asif Raza; Adeel Anwaar; Riyan Imtiaz Karamat; Aymar Akilimali; Inam Ul Haq Arain (Clinical Case Reports)
ABSTRACT Self‐insertion of foreign bodies into the urethra is uncommon and is often associated with complex psychological or behavioral factors. Many cases of foreign bodies in the urethra have been reported worldwide with variable complaints of penile pain, penile itching, dysuria, hematuria, and complete obstruction of urine. These foreign objects are managed to remove according to their size, complexity of shape, and location in the urethra. We report a case of a self‐inserted sewing needle in the urethra by an old man during an act of achieving sexual gratification, which was removed through an endoscopic approach by cystoscopy, along with a literature review. This is the fourth reported case of auto‐eroticism in which a sewing needle was used to achieve sexual pleasure, making this case report a rare one.